The impact of corporate governance and intellectual capital on firm's performance and corporate social responsibility disclosure - Shoaib Aslam; Muhammad Ahmad; Shahid Amin; Muhammad Usman; Shafaq Arif (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
Whether the corporate governance (CG) and intellectual capital (IC) affects the firms' financial performance and corporate social responsibility (CSR) disclosure of Australian stock exchange (ASX) listed firms or not? To answer this crucial question we use the data of all firms listed at ASX for the year 2014. Using the Partial Least Square based Structural Equation Modeling (PLS-SEM) we find reliable evidence that the main driving force behind the CSR disclosure in ASX listed firms is CG rather than IC. These results suggest that, the firms with sound corporate governance practices are more environment-friendly. In addition, we also find that both CG and IC are associated with improved firm financial performance. Our study is helpful for both Australian government and regulatory bodies that are keenly interested in improving the policies on the issues of global warming (i.e. climate change, carbon emission trading schemes, and preservation of natural capital) by providing the empirical evidence that the strong CG practices are not only beneficial for the shareholders but also for the society.
Keywords: 330; corporate governance; intellectual capital; corporate social responsibility; Australian stock exchange (ASX); PLS-SEM; NVIVO